2012
DOI: 10.3389/fmicb.2012.00043
|View full text |Cite
|
Sign up to set email alerts
|

Iron Utilization in Marine Cyanobacteria and Eukaryotic Algae

Abstract: Iron is essential for aerobic organisms. Additionally, photosynthetic organisms must maintain the iron-rich photosynthetic electron transport chain, which likely evolved in the iron-replete Proterozoic ocean. The subsequent rise in oxygen since those times has drastically decreased the levels of bioavailable iron, indicating that adaptations have been made to maintain sufficient cellular iron levels in the midst of scarcity. In combination with physiological studies, the recent sequencing of marine microorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 143 publications
6
123
1
1
Order By: Relevance
“…When compared with lactate-grown co-cultures (Supplementary Table S7), Synechococcus 7002 transcription profiles displayed downregulation of photorespiration and carbohydrate metabolism genes during co-culturing with HCO 3 À . These patterns as well as elevated transcript levels of Fe acquisition genes (Table 5) are more likely to be linked to the increased production of light-capturing and photosynthetic machinery (Ludwig and Bryant, 2012;Morrissey and Bowler, 2012) and higher CO 2 availability (Table 1). Similarly, lower mRNA levels of putative nitrile/cyanate, dipeptide and amino acids transporter genes suggested decreased need for additional (organic) carbon sources during photoautotrophic growth of Synechococcus 7002.…”
Section: Identification Of Putative Interactions Through Metabolite Pmentioning
confidence: 99%
“…When compared with lactate-grown co-cultures (Supplementary Table S7), Synechococcus 7002 transcription profiles displayed downregulation of photorespiration and carbohydrate metabolism genes during co-culturing with HCO 3 À . These patterns as well as elevated transcript levels of Fe acquisition genes (Table 5) are more likely to be linked to the increased production of light-capturing and photosynthetic machinery (Ludwig and Bryant, 2012;Morrissey and Bowler, 2012) and higher CO 2 availability (Table 1). Similarly, lower mRNA levels of putative nitrile/cyanate, dipeptide and amino acids transporter genes suggested decreased need for additional (organic) carbon sources during photoautotrophic growth of Synechococcus 7002.…”
Section: Identification Of Putative Interactions Through Metabolite Pmentioning
confidence: 99%
“…The composition of Fe transporters analyzed here is not unique. Many microorganisms possess the genetic potential for multiple iron transporters (Rivers et al, 2009;Desai et al, 2012;Hopkinson and Barbeau, 2012;Morrissey and Bowler, 2012). Bioinformatic analyses of iron transport genes revealed that fut genes are common in cyanobacteria (Rivers et al, 2009;Hopkinson and Barbeau, 2012, with additional analysis included in Supplementary Figure S4).…”
Section: Coordinated Transporter Activity C Kranzler Et Almentioning
confidence: 99%
“…This pathway is well-characterized in eukaryotic phytoplankton (Jones et al, 1987;Soria-Dengg and Horstmann, 1995;Maldonado and Price, 2001;Shaked et al, 2005;Allen et al, 2007;Morrissey and Bowler, 2012) and involves plasma membrane reductases that promote the reductive dissociation of organically bound Fe(III). In contrast to substrate-specific siderophore-mediated iron uptake, this strategy grants phytoplankton access to a wide range of organic and inorganic Fe(III) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they undergo major architectural changes in photosynthetic membranes involving the over-expression of photosynthetic pigments (Ryan-Keogh et al, 2012), the use Fe-economic pathways for ATP synthesis (Bailey et al, 2008), and the reduction of their Fe requirements (Behrenfeld and Milligan, 2013). In addition, some cyanobacteria have also developed specific high-affinity Fe uptake strategies (Morrissey and Bowler, 2012;Kranzler et al, 2014) such as production of siderophores that enhance Fe bioavailability in their immediate environment (Sunda, 2012). Thus, these complex biological interactions with Fe chemistry challenge the quantification of Fe bioavailability in marine environments.…”
Section: Introductionmentioning
confidence: 99%